Pengaruh Komunikasi dan Iklim Organisasi Terhadap Loyalitas Kerja Karyawan - Aidil Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Work loyalty is an employee's loyalty to the company and the responsibility given by the company in the form of trust that keeps company secrets and the employee's willingness to advance the company Communication is a process of delivering messages from a person who gives or sends messages to the recipient of the message in the form of ideas or information transfer. Organizational climate is a condition, condition and characteristic of the work environment that characterizes an organization which is formed from the attitudes, behavior and personality of all members of the organization.This research uses quantitative descriptive research. The sampling technique uses a saturated sample where the entire population will be used as the research sample. The measurement scale used is a Likert scale.Partially and simultaneously there is a significant influence between communication variables and organizational climate on work loyalty.